2015
DOI: 10.1590/1678-4162-8224
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization study of dogs with atopic dermatitis in the central region of Rio Grande do Sul

Abstract: Canine atopic dermatitis (CAD) is a common dermatosis, defined as a genetic-related disease which predisposes to skin inflammation and pruritus, associated to a IgE-specific response in most of cases. Clinical diagnosis may be later complemented by skin allergy and/or serological tests. The aim of these tests is to identify possible allergens in order to enable the clinicians to select candidate antigens for allergen specific immunotherapy. In the present study 58 CAD positive animals were tested. All were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Sensitization to CD was detected in 16.8 and 80% of patients with rhinitis in Curitiba (Araújo et al, 2015) and Rio Grande do Sul (Vieira et al., 2011), respectively. A previous study using IDT in Brazil found that 24.13% of atopic dogs were sensitized to CD (Pereira et al, 2015). In the present study, the positive response to this grass was similar to the other studies cited.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Sensitization to CD was detected in 16.8 and 80% of patients with rhinitis in Curitiba (Araújo et al, 2015) and Rio Grande do Sul (Vieira et al., 2011), respectively. A previous study using IDT in Brazil found that 24.13% of atopic dogs were sensitized to CD (Pereira et al, 2015). In the present study, the positive response to this grass was similar to the other studies cited.…”
Section: Discussionsupporting
confidence: 92%
“…In dogs, the prevalence of grass pollen sensitization ranges from 10 to 27.7% (Masuda et al, 2000;Roussel et al, 2013). In Brazil, one study using IDT identified 10.3% of sensitization in atopic dogs using grass polens extracts (Pereira et al, 2015). In the present study using PT, the prevalence of sensitization to grass pollen was (25.6%) and CD and LM were the most important species.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Therefore, the aim of the present study was to evaluate the influence of oclacitinib and prednisolone on IDT and PT immediate-phase reactions in dogs diagnosed with atopic dermatitis, sensitised to environmental allergens commonly involved as inciting allergens in Brazil. [18][19][20]…”
Section: O R I G I N a L A R T I C L E A Randomised Double-blinded Tr...mentioning
confidence: 99%